Toxicological aspect of immunomodulators: friend or foe in increasing the effectiveness of cancer immunotherapy - Djukić-Ćosić, Danijela (Archives of Pharmacy, 2022)
Malignant diseases world incidence is constantly increasing and it is assumed that combining immunomodulators with immunotherapy would improve cancer therapy effectiveness. We present a research-development project of international cooperation with the People's Republic of China entitled "Increasing the effectiveness of cancer immunotherapy with a combination of CAR-T cells or PD-1/PD-L1 inhibitors using immunomodulators", led by Faculty of Pharmacy, University of Belgrade. Sulforaphane (SFN), isothiocyanate from cabbage vegetables, and a type of inactivated bacterium Pseudomonas aeruginosa (PA-MSHA) have been recognized as immunomodulators with high immune system stimulating potential, i.e. antitumor effect. However, there are few data on their individual safe use, and no data on the potential side/harmful effects of their combination, especially in patients with malignant diseases and significant immune system impairment. The Chinese team is investigating the effectiveness of improving immunotherapy with combination of immunomodulators, with their first published results proving SFN positive effect when administered with CAR-T cells, while Serbian team aims to examine toxicological profiles of single and/or combined SFN and PA MSHA, in silico, in vitro and in vivo on two experimental models - zebrafish and rat. The project will specifically examine adverse effects potential of single and/or combined use of the tested immunomodulators or lack of their efficacy in cancer patients, especially colon cancer. The first in silico results of the Serbian team indicated benefit/risk of SFN in patients with colon cancer depending on individual genes expression and identified gene set which change may indicate a positive or negative effect of immunomodulators.